Level of Implementation of Practical Activities in Science Laboratories of Junior High School - Amrina Yusra; Indah Taqwilawaty; Yusli Kamila; Muhammad Rahmad; Roza Linda (Universitas Lambung Mangkurat, 2026)
Practical work is an essential part of science learning because it provides students with hands-on experience to deeply understand concepts. To determine its effectiveness, a case study was conducted at SMPN 3 Siak Hulu with 60 students through questionnaires and observations. The results showed a significant gap: students' perceptions of practical work were in the